Seat-Occupancy Detection System and Breathing Rate Monitoring Based on a Low-Cost mm-Wave Radar at 60 GHz - Antonio Lazaro; Marc Lazaro; Ramon Villarino; David Girbau (IEEE Access, 2021)
This work presents a seat-occupancy detection system based on a PCR (Pulsed Coherent Radar) at the unlicensed 60 GHz ISM band. The radar can measure distances with sub-millimeter resolution. Therefore, the system can detect the presence of people occupying the seats by measuring small movements of the body, such as those produced by breathing. In consequence, the system not only measures seat-occupancy but also breathing rate, which is estimated from the amplitude peaks after filtering the amplitude measured by the radar to remove the noise. The effect of the car vibrations and random body movement is experimentally studied. Measurements performed with adults, as well as with a baby emulator sitting in a child seat, are presented. Comparison of the system with another that measures the breath based on airflow shows good agreement and permits its validation.